Prehispanic and colonial landscape change and fluvial dynamics in the Chalco Region, Mexico (2018)
© 2018 Elsevier B.V. The late Quaternary deposits of the lakeshore plain and western edge of Lake Chalco in the southeastern Basin of Mexico were explored in order to understand the influence of alluvial sedimentation on archeological visibility and preservation, as well as to seek out records that would permit direct comparison of erosion and sedimentation with the demographic record derived from the archeological survey. The Chalco lakeshore plain is traversed by two of the largest rivers in the region, and the pattern of human settlement recorded here by archeological survey is partly an artifact of alluvial sedimentation, where the most prominent settlements were observed in areas with little or very slow sedimentation. Detailed radiocarbon dating of the alluvial deposits indicates that prior to the establishment of a sedentary lifestyle, alluvial sedimentation was slow. Catastrophic soil erosion is inferred from a period of widespread rapid alluviation and mass movements during late Preceramic, Early and Middle Formative periods, which were periods of rapid population growth. Mass movements appear to coincide also with periods of wetter climate. No evidence of sedimentation was noted during the population collapse that occurred at the end of the Formative. The next phase of alluvial sedimentation occurred during the Early Classic to Late Toltec periods, which were also periods of population expansion during a gradually drying climate. The Postclassic period, which was the largest Pre-Columbian demographic expansion, was paradoxically accompanied by minor evidence of alluvial activity. The last and most widespread period of alluvial activity occurs in the post-Conquest period and is difficult to date with precision but appears to occur primarily during the seventeenth and eighteenth centuries.